CHARACTERISTICS OF VEGETABLE FARMERS AND THEIR IMPLICATIONS FOR THE APPLICATION OF FARMING TECHNOLOGY - Firdaus, Firdaus; Adri, Adri; Suharyon, Suharyon; Edi, Syafri (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
The Paal Merah Village area, Paal Merah Jambi District, City is dominated by dry land with a wet climate, so the developing farming pattern is based on dry land with a wet climate. This paper aims to study the characteristics of farmers in dry land with wet climates and their implications for the application of farming technology. The research was conducted in Paal Merah Village, Paal Merah District, Jambi City, in 2020, involving 25 farmers who were randomly selected as respondents. Through descriptive data analysis, the following picture is obtained: First, vegetable farming at the research location has the potential to be developed intensively and sustainably. Second, support from the characteristics of farmers of productive age, a fairly high level of education, and farming experience will motivate farmers. To increase its business intensively. Third, opportunities to increase farming productivity are still wide open through optimizing the use of potential farming land resources based on farmers' strengths and weaknesses. Fourth, to increase productivity in dry land areas with wet climates, the strategy is to diversify businesses (multi enterprises); implementing integrated farming patterns, accelerating technology dissemination and encouraging the growth of partnership collaboration networks. For the multi-enterprise strategy to be implemented, it is necessary to have a soft credit scheme policy whose implementation is accompanied by assistance from extension workers and researchers.